RISK FACTORS FOR SUICIDAL BEHAVIOR MOOD DISORDERS IN ADULTS AND ADOLESCENTS - Juraev Shohrukh Djumanazarovich (Galaxy International Interdisciplinary Research Journal, 2022)
This article states that currently suicide attempts and suicide among adults and adolescents is common and major global clinical and public health problem health among psychiatric patients. It was mentioned that identifying risk factors for certain types of underlying affective disorders can help determine suicide risk, support preventive measures and treatment of patients from risks and improvement forecast. In particular, bipolar disorders and depressive disorder have a particularly high risk of mental illness.